MENYOAL HAK NORMATIF PEKERJA/BURUH DALAM PROSES INDUSTRIALISASI - Teguh Sulistia; Aria Zurnetti (Perspektif, 2004)
Protection of normative right of the workers in Indonesia still weakness and necessary improve by government or labour organization. The workers are treated dishonour by employers in work relationship on industrialization process. Tripartite relationship is not running well too due government always to save employers than workers. It’s impact, conflict between employers and workers can not avoid again. Harmonization of work relationship could be done through human resources development and law protection of normative rights for workers.